Al-Lām al-Mufradah Bayna Ittiḥād al-Māddah wa Taʿaddud al-Waẓīfah - Muhammad Sayyed Hagag (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
This research focuses on the Arabic letter Lām, which plays a significant role in speech due to its frequent occurrence, widespread usage, distinctive phonetic characteristics, various modes of pronunciation, and multiple grammatical functions. The study examines the unity of the letter's phonetic form while highlighting the diversity of its grammatical functions. The research investigates the different functions of the governing (ʿāmilah) Lām, including Lām al-Jarr (the prepositional Lām), Lām al-Tawkīd (the emphatic Lām), and Lām al-Amr (the imperative Lām). It also discusses the various types and functions of the non-governing (ghayr al-ʿāmilah) Lām, classifying them according to their respective grammatical roles. To illustrate these functions, the study uses examples of the letter Lām in the Qur'an, particularly in Sūrat al-Kahf, because of the richness and diversity of its linguistic applications. The research also presents statistical data on the occurrence of the letter Lām in the sūrah and analyzes selected Qur'anic verses to demonstrate its different grammatical and semantic functions. The findings reveal that the governing Lām performs several major functions within Arabic sentence structure, including the prepositional, emphatic, and imperative Lām. Likewise, the non-governing Lām serves numerous functions, such as the Lām of oath, the initial Lām (Lām al-Ibtidāʾ), the Lām of specification or attribution, and several other grammatical uses.